Fiscal Decentralization Policy and Its Impact on the Development of Underdeveloped Regions in South Sulawesi - Dwiyanti, Andi Amytia Resty; Irmawati, Irmawati; Syam, Anita; Asriadi, Asriadi (Jurnal Ilmu Administrasi Negara (JUAN), 2025)
Fiscal decentralization has been a key element of Indonesia’s regional autonomy policy, aiming to distribute authority and resources from the central to local governments to foster equitable development. Despite substantial increases in fiscal transfers through mechanisms such as the General Allocation Fund (DAU) and Special Allocation Fund (DAK), underdeveloped regions in South Sulawesi continue to face persistent development gaps in infrastructure, public services, and socioeconomic outcomes. This study aims to examine the implementation of fiscal decentralization policies and their impact on the development of underdeveloped districts in South Sulawesi, focusing on the interplay between fiscal transfers, local governance capacity, and geographic constraints. Using a qualitative library research method, data were collected from government regulations, official reports, statistical data, and scholarly literature, and analyzed through content analysis to identify key themes related to policy objectives, implementation, and development outcomes. The findings reveal that while fund allocation and disbursement rates are generally high, the developmental impact is constrained by weak budget planning, limited technical capacity, poor inter-agency coordination, and the dominance of routine expenditures over capital investments. Geographic challenges, particularly in remote and island districts, further inflate development costs and delay project completion. The study concludes that fiscal decentralization in South Sulawesi requires comprehensive reform, including differentiated allocation formulas, performance-based incentives, enhanced technical assistance, and stronger accountability mechanisms. Such measures are essential to ensure that fiscal decentralization achieves its intended goal of promoting inclusive, equitable, and sustainable regional development.